2013
DOI: 10.1186/0778-7367-71-26
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of obesity among primary school children in Dar es Salaam, Tanzania

Abstract: BackgroundChildhood obesity has increased dramatically and has become a public health concern worldwide. Childhood obesity is likely to persist through adulthood and may lead to early onset of NCDs. However, there is paucity of data on obesity among primary school children in Tanzania. This study assessed the prevalence and determinants of obesity among primary school children in Dar es Salaam.MethodsA cross sectional study was conducted among school age children in randomly selected schools in Dar es Salaam. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
49
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 39 publications
(50 reference statements)
9
49
6
Order By: Relevance
“…Study done in Douala, Cameron in 2010, the prevalence of overweight ranges from 6.4% to 8.2% in boys and from 10.7% to 17.2% in girls, whereas prevalence of obesity ranges from 1.4% to 5.5% in boys and from 2.4 to 8.6% in girls. Prevalence of underweight according to WHO 2007 reference was higher in boys as compared to girls, 5.5% and 9.2% respectively [20]. The sex specific prevalence of underweight was almost equal in our study 22 (9.9%) male and 22 (9.1%) female.…”
Section: Prevalence Of Overweight And/or Obesitycontrasting
confidence: 38%
See 1 more Smart Citation
“…Study done in Douala, Cameron in 2010, the prevalence of overweight ranges from 6.4% to 8.2% in boys and from 10.7% to 17.2% in girls, whereas prevalence of obesity ranges from 1.4% to 5.5% in boys and from 2.4 to 8.6% in girls. Prevalence of underweight according to WHO 2007 reference was higher in boys as compared to girls, 5.5% and 9.2% respectively [20]. The sex specific prevalence of underweight was almost equal in our study 22 (9.9%) male and 22 (9.1%) female.…”
Section: Prevalence Of Overweight And/or Obesitycontrasting
confidence: 38%
“…Limited number of research in this area motivates us to select this topic. Though, there is a lack of data concerning overweight and obesity assessment in childhood and adolescence in Ethiopia, clearly the risk of childhood obesity leading to adult morbidity is of great public health significance [15][16][17][18][19][20].…”
mentioning
confidence: 99%
“…In 2008, locally published study done in Al-Hassa showed that the prevalence of overweight of primary school boys was 14.2% while that of obesity was 9.7%, but the age range in that study was 10-12 years [25]. In a study conducted among primary school children in Riyadh (2013), a prevalence of 16% and 11% for overweight and obesity were reported among school boys [32].…”
Section: Discussionmentioning
confidence: 97%
“…Recent study done in Riyadh and published at 2008 showed that prevalence of obesity in primary school girls was 14.9% [38]. In a study conducted among primary school children in Riyadh (2013), a prevalence of 20% and 17% for overweight and obesity were reported among school girls [32]. Al-Shehri et al [39] carried out a review is to evaluate the prevalence and the trends of obesity among Saudi children (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012).…”
Section: Discussionmentioning
confidence: 99%
“…Data collection procedures for this study have already been described elsewhere (Muhihi et al, 2013). Anthropometric measurements were taken early in the morning before classes began.…”
Section: Anthropometricsmentioning
confidence: 99%